2012
DOI: 10.1111/j.1740-8709.2011.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

A one‐year school‐based diet/exercise intervention improves non‐traditional disease biomarkers in Mexican‐American children

Abstract: School-based interventions are an effective way to treat childhood obesity. The purpose of the present study was to biologically validate an established school-based intervention designed to reduce standardised body mass index (zBMI) over a period of 12 months. This intervention focused on a subset of Mexican-American children who were participating in a larger clinical weight loss study. Plasma samples were analysed from self-identified Mexican-American children (12-14 years) who were randomised to either a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 19 publications
(93 reference statements)
3
31
0
Order By: Relevance
“…We have previously demonstrated that weight gain and obesity alter the profile of monocytes in both humans and mice (9,21). Our findings with respect to leptin, MCP-1, and TNF-a are consistent with previous reports from our laboratory and others (9,10). This finding is interesting because it appears that leptin and MCP-1 may be more responsive to smaller differences in body fat than TNF-a.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have previously demonstrated that weight gain and obesity alter the profile of monocytes in both humans and mice (9,21). Our findings with respect to leptin, MCP-1, and TNF-a are consistent with previous reports from our laboratory and others (9,10). This finding is interesting because it appears that leptin and MCP-1 may be more responsive to smaller differences in body fat than TNF-a.…”
Section: Discussionsupporting
confidence: 92%
“…The subjects in this study were participating in a larger clinical weight loss study that has been in existence since 2003 and has been described in a number of previous publications (6,(8)(9)(10)(11). The subjects attended a charter school, whose population was predominantly Mexican American (>95%).…”
Section: Subjectsmentioning
confidence: 99%
“…Our area of research focuses on a study of how exercise and dietary habits influence immune system health and function 6,[8][9][10][18][19][20] . Such objectives have significant practical implications for a variety of areas of human health.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past ten years, our laboratory, among others, has been keenly focused on the effect of various nutritional and exercise treatments patterns on innate immune function [6][7][8][9] . The method demonstrated in this manuscript has practical implications within the field of clinical immunology.…”
Section: Introductionmentioning
confidence: 99%
“…() reported that training of community workers to work with parents in delivering the Health Exercise Nutrition for the Really Young (HENRY) programme through Sure Start Centres had a number of benefits, including the provision of age‐appropriate portion sizes and increased staff confidence regarding tackling lifestyle changes and working with families. Schools provide numerous opportunities for prevention because it is possible to provide access to healthy meals and snacks (Madden et al ., ), exercise (McFarlin et al ., ), health education and more personalised interventions. Elizondo‐Montemayor et al .…”
mentioning
confidence: 99%